The Impact of the School Grade on the Significance of the Motivating and Demotivating Factors in Foreign Language Learning - EL OUANJLI, HANAN; Anasse, Khadija; Lahri, Mohamed (International Journal of Linguistics and Translation Studies, 2023)
Promoting autonomous learning has been of much concern in second/foreign language acquisition for decades. Corroborating evidence from theoretical and empirical research in this field has asserted the importance of several factors in attaining this goal. Motivation has been a critical factor that enables learners to become self-directed and successful. Yet, it has been demonstrated that the motivation level may vary due to the influence of some internal and external factors. Therefore, the purpose of this study aims. To this end, 178 students took part in filling in a questionnaire. The data were analysed statistically using the Statistical Package for the Social Science (SPSS) software, version 20. The study’s results revealed that Moroccan learners were interested in learning English, but their motivation levels varied significantly. This variation was ascribed to the effect of several motivating and demotivating factors, which were, in turn, substantially affected by the school grade of students. Hence, it is crucial to consider the impact of this variable on such factors to control their influence on learners’ motivation.